Necessity and Truthful Fictions : Panenmentalist Observations. - Gilead, Amihud. (Value Inquiry Book Series, 2009)
This book discovers areas and themes, especially in philosophical psychology, for novel observations and investigations, the diversity of which is systematically unified within the frame of the author's original metaphysics, panenmentalism. The book demonstrates how by means of truthful fictions we may detect meaningful possibilities as well as their necessary relationships that otherwise could not be discovered.